PERAN KALIGRAFI ISLAM DALAM PENYEBARAN NILAI-NILAI SYARIAH - Nazira Aprilia Asty (Jurnal Ekshis, 2025)
Islamic calligraphy is not only a beautiful visual art but also an effective medium for conveying Islamic values, including the principles of sharia-based economics. This study aims to explore the role of Islamic calligraphy in disseminating the values of Islamic economics, such as justice, honesty, zakat, charity, and the prohibition of usury. A qualitative approach with a literature study method was employed to analyze the relationship between calligraphic art, sharia values, and its potential for education and da'wah. The findings reveal that Islamic calligraphy possesses aesthetic and symbolic power capable of capturing attention and delivering moral and spiritual messages profoundly. Various calligraphy works, inspired by verses from the Qur'an and hadith, often reflect sharia economic values, such as encouragement for charitable acts through zakat and charity, as well as warnings against the practice of usury. Furthermore, calligraphy serves as an educational tool for society to comprehend and internalize Islamic economic principles. This study concludes that Islamic calligraphy is not merely a cultural heritage but also a relevant medium for promoting sharia-based economic principles in Muslim communities. Further research is recommended to explore the integration of Islamic art with other fields in modern life.